2011
DOI: 10.3109/01443615.2011.568073
|View full text |Cite
|
Sign up to set email alerts
|

FlowCytomix analysis forToxoplasma gondiiinfection in pregnant women in central Taiwan

Abstract: The study was to determine the seroprevalence of toxoplasmosis in the sera of pregnant women in central Taiwan and to investigate the levels of cytokine in the sera of pregnant women with Toxoplasma gondii infection. The 220 blood samples were collected from pregnant women. The haematological parameters of peripheral blood were analysed by a haematology analyser. Serum samples of the pregnant women were analysed by a commercially available anti-T. gondii IgM/IgG antibody enzyme-linked immunosorbent assay (ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…The overall seroprevalence in the 104 pregnant women evaluated in this study was 7.7z (8/104). Our results indicated that the seroprevalence of toxoplasmosis among pregnant women in Taipei was much lower than that reported among aboriginal pregnant women (40.6z) and immigrant pregnant women (18.2z) in Central Taiwan (22), but was similar to that reported in a previous study on Taiwanese pregnant women in Taipei (9.1z) (19), and in Central Taiwan (11.8z) (23). Compared with neighboring countries, the overall seroprevalence in the present study was similar to that reported in Japan (10.3z) (13), and in Changchun, northern China Toxoplasma in Pregnant Women in Taipei City (10.6z) (16); however, the overall seroprevalence in the present study was higher than that reported in South Korea (4z) (12).…”
Section: Discussionsupporting
confidence: 88%
“…The overall seroprevalence in the 104 pregnant women evaluated in this study was 7.7z (8/104). Our results indicated that the seroprevalence of toxoplasmosis among pregnant women in Taipei was much lower than that reported among aboriginal pregnant women (40.6z) and immigrant pregnant women (18.2z) in Central Taiwan (22), but was similar to that reported in a previous study on Taiwanese pregnant women in Taipei (9.1z) (19), and in Central Taiwan (11.8z) (23). Compared with neighboring countries, the overall seroprevalence in the present study was similar to that reported in Japan (10.3z) (13), and in Changchun, northern China Toxoplasma in Pregnant Women in Taipei City (10.6z) (16); however, the overall seroprevalence in the present study was higher than that reported in South Korea (4z) (12).…”
Section: Discussionsupporting
confidence: 88%
“…This finding fell within the range of 2.6% - 28% of seroprevalence that have been reported in Thailand [10-18]. However, our prevalence rate is still higher compared to previous studies conducted recently in our Asian counterparts such as China, Japan and Taiwan being 3.98%, 10.3% and 11.8%, respectively [19-21]. Globally, the seroprevalence of Toxoplasma infection remains high in many countries across the continents, e.g., 84.7% in Congo [22], 83.6% in Ethiopia [23], 45% in India [24], 59% in Brazil [25] and 30.9% in Tanzania [26].…”
Section: Discussionsupporting
confidence: 81%
“…Several high‐content protein microarrays for comparative profiling are available commercially (Tables and ) , however, of these, relatively few have been validated for in vitro diagnostics (IVD) applications; moreover, despite the theoretical multiplexing capacities of the platforms, commercially available panels appear to only harness a fraction of this capacity, seldom exceeding 20 individual analytes . Contemporary multiplex immunoassay systems may be divided into the two described formats: planar assays and microbead‐based suspension assays (Fig.…”
Section: Commercially Available Multiplex Immunoassaysmentioning
confidence: 99%